Systematic literature review: towards an industry 4.0 maturity model - Casonatto, Ricardo Accorsi; Santos, Maria Isabel Araújo Silva dos; Oliveira, Edgard Costa (Brazilian Journal of Production Engineering, 2023)
Nowadays, compared to the 4th Industrial Revolution, the industry needs to be competitive, innovative and incorporate digital technologies. This challenge and quest for competitiveness needs support in view of the escalation of potential maturity levels that a company can reach, which makes it essential to measure business maturity. maturity in Industry 4.0. using the Consolidated Meta-Analytic Approach Theory (TEMAC) to identify impact literature and bibliometric analyses. Based on the analysis of several articles found, criteria were identified for a maturity model for industry 4.0, namely: assistance from partners, suppliers and customers, as well as qualified labor, use of consumer data and strategic vision open to innovation. The concern with SMEs in this literature was evident, which are more numerous and prone to launch themselves in industry 4.0. This research also revealed the opportunity to develop a specific maturity model capable of meeting the recent demand for a theoretical and practical framework that helps measure the maturity of companies in Industry 4.0.